PENGARUH UKURAN KOMITE AUDIT, KEPEMILIKAN PUBLIK, UKURAN DEWAN KOMISARIS, DAN RISK MANAGEMENT COMMITTEE TERHADAP PENGUNGKAPAN MANAJEMEN RISIKO - Yunita Pratiwi (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to analyze the effect of audit committee, public ownership, size of the board of commissioners, and risk management committe on the risk management disclosures. The population in this study are banking sector companies listed on the Indonesia Stock Exchange (IDX) in 2017- 2021. The sampling technique in this study used purposive sampling and found 205 observations. The data analysis model used by this study is data panel regression analysis using EViews software. The results showed that the audit committee, public ownership, size of the board of commissioners, and risk management committe simultaneously had a significant impact on the risk management disclosures. Meanwhile, partially the audit committee, public ownership, the size of the board of commissioners and risk management committe has no a significant effect on the official website on the timeliness of financial statement reporting. The size of the board of commissioners has an effect on risk management disclosures.